UPAYA PENINGKATAN MINAT BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MENGGUNAKAN CTL PADA SISWA KELAS IV SEKOLAH DASAR - Dwi Nurfathiyah (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
In today's era, students tend to show a lack of interest in mathematics. Therefore, the purpose of this study is to foster students’ learning interest in mathematics. The research was conducted at SDN Karang Mekar 1 using a quantitative method. The results showed a pre-test score of 58.21 and a post-test score of 89.29. The feedback sheet results totaled 881 out of a maximum of 1,120, indicating a success rate of 78.66%. The closed-ended questionnaire instrument scored 1,289 out of a maximum of 1,568, reflecting a success rate of 82.23%. The researcher investigated students’ interest in the topic of bar charts and efforts to improve that interest through the use of an interactive learning model. The study concluded that students were able to engage actively in the learning process through the use of the Contextual Teaching and Learning (CTL) model, which effectively increased their interest in learning. Thus, it is important for educators to utilize interactive media or learning models to foster students' learning interest.